Analisis Kesalahan Siswa dalam Menyelesaikan Soal Pemahaman Konsep Pada Materi Integral - fara, Faradiba bila (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The ability to understand students' concepts is very important to be applied to learning mathematics. When students cannot understand the concept well, students cannot solve the problem correctly. This is the reason the researcher conducted this research. The purpose of this research is to describe the percentage of students' errors in solving the problem of understanding the concept of integral matter. The subjects in this study were class XII students, totaling 8 students. Data collection techniques used were observation and tests to see student errors in answering questions of understanding the concept. This study uses a quantitative approach with a descriptive type of research. The data analysis technique used the percentage of students' ability assessment in solving problems. The results obtained in this study are the indicator of error reading about the questions gets a percentage of 62.5%, then the percentage of errors in understanding the questions gets a value of 50%, the percentage of transformation errors gets a value of 75%, then on the percentage of error processing skills gets a score of 62.5% and the percentage of errors in writing the final answer also obtained the same results as the percentage of process skills errors, which was 62.5%. This is because most students do not understand the integral concept so they do not understand in determining the formula and applying it. the percentage of transformation errors gets a value of 75%, then the percentage of process skills errors gets a value of 62.5%, and the percentage of errors in writing the final answer also gets the same result as the percentage of process skills errors that is 62.5%. This is because most students do not understand the integral concept so they do not understand in determining the formula and applying it. the percentage of transformation errors gets a value of 75%, then the percentage of process skills errors gets a value of 62.5%, and the percentage of errors in writing the final answer also gets the same result as the percentage of process skills errors that is 62.5%. This is because most students do not understand the integral concept so they do not understand in determining the formula and applying it